Measurement of dynamical ski behavior during alpine skiing - Fauve, M.; Auer, M.; Lüthi, A.; Rhyner, H.; Meier, J. (Science and Skiing IV, 2009)
INTRODUCTION: The mechanical properties of a ski can considerably influence the performance and sensations felt by skiers (Fischer et al., 2007). It remains unknown whether laboratory measurements can enable one to predict the behaviour of a ski when it is being used on the snow. The purpose of the present study was to develop a method for measuring ski deformation during skiing and to quantify the influence of snow strength and loading condition on ski deformation.